Quality of the municipal service and satisfaction of the citizens of Piura 2021 - Caballero Marreros, Edson Johan (2022)
The objective of the research has been to determine the relationship between the quality of the municipal service and the satisfaction of the citizens of Piura 2021. To meet this objective, we collected data using the survey technique and, as an instrument, the questionnaire, which we applied to a random sample of 384 citizens. Once the data was collected, we created a database using SPSS Version 25, from which we described the variables (descriptive statistics) and the corresponding hypothesis tests (inferential statistics). The main conclusion we have reached, with the investigation, has been that there is a significant relationship between the quality of the municipal service and the satisfaction of the citizens of Piura 2021.